Analysis on Managing Anger Epidemic to Avoid Domestic Violence, Spousal Abuse Elder Abuse and Child Abuse: Understanding the Link between Anger and Domestic Violence (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Domestic Violence prompts 25 percent of genuine physical assaults on woman, men, elders, spouses and even children and about 33 of every single female crime. Domestic Violence emerges, when one accomplice tries to overwhelm or control the other accomplice by force or by manipulation physically, emotionally, psychologically or mentally or even financially [1, 2]. Violence isn't an issue of stress it is an issue of blundered anger. There is no violence without anger. Violence is an enthusiastic reaction to being harmed or debilitated. The epidemic of shootings and ambushes are not silly wrongdoings, they are violations of anger.